2013
DOI: 10.1111/apps.12016
|View full text |Cite
|
Sign up to set email alerts
|

The Conceptualisation and Measurement of Pacing Styles

Abstract: Pacing style reflects how individuals distribute their effort over time in working toward deadlines. As a new construct introduced in 2002, the notion of pacing style has intuitive appeal, but has been under-researched, in part, due to a measurement need. Therefore, the purpose of this research was to improve the conceptualisation of pacing style and to develop and validate a new scale-based measure. The result was the nine-item Pacing Action Categories of Effort Distribution (PACED), consisting of deadline (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 88 publications
1
53
0
Order By: Relevance
“…This construct is based on the passage of objective time, with some studies implicitly addressing the timing issues of rate (how long one works) and scheduling (when this work is scheduled). Typically, an individual prefers either (a) a deadlineoriented style, in which individuals procrastinate until the deadline is on the verge of passing; (b) a steady style, in which individuals maintain consistent effort from beginning to end of a project; or (c) an early, or U-shaped, style, in which much effort is devoted early in a project and may resume as the deadline approaches (Gevers et al 2006(Gevers et al , 2013. Although empirical evidence is just emerging, studies have shown that challenge-related strain is more common for those with a deadline style or a U-shaped style (i.e., pressure is greater from the impending deadline), but that task absorption is greater for those with a steady style or a U-shaped style (i.e., earlier action allows one to lose oneself in a task; Gevers et al 2013).…”
Section: Time-related Constructsmentioning
confidence: 99%
“…This construct is based on the passage of objective time, with some studies implicitly addressing the timing issues of rate (how long one works) and scheduling (when this work is scheduled). Typically, an individual prefers either (a) a deadlineoriented style, in which individuals procrastinate until the deadline is on the verge of passing; (b) a steady style, in which individuals maintain consistent effort from beginning to end of a project; or (c) an early, or U-shaped, style, in which much effort is devoted early in a project and may resume as the deadline approaches (Gevers et al 2006(Gevers et al , 2013. Although empirical evidence is just emerging, studies have shown that challenge-related strain is more common for those with a deadline style or a U-shaped style (i.e., pressure is greater from the impending deadline), but that task absorption is greater for those with a steady style or a U-shaped style (i.e., earlier action allows one to lose oneself in a task; Gevers et al 2013).…”
Section: Time-related Constructsmentioning
confidence: 99%
“…Identifying and understanding the period of a task during which people are working most slowly is necessary for developing nuanced theories and practical interventions to ameliorate these lulls. Multiple studies have unearthed various pacing patterns, such as the deadline effect, whereby workers progressively speed up as a deadline approaches (Lim & Murnighan, 1994); mid-point transitions, whereby workers tend to speed up suddenly at the midpoint of a task (Gersick, 1988(Gersick, , 1989; and U-shaped pacing, whereby work pace is fastest at the beginning and end of a task (Gevers, Mohammed, & Baytalskaya, 2015;Gevers, Rutte, & Van Eerde, 2006). Although a number of pacing patterns have been delineated (Gevers et al, 2015), research on these patterns generally shares one commonality: the assumption of tightly limited time to work, which causes workers to speed up (in some manner) as a deadline approaches.…”
Section: The Work Pacing Consequences Of Idle Time Idle Time and Pacimentioning
confidence: 99%
“…The result suggests that procrastination is conducive to creative performance, as individuals had used the time to scrutinize available solutions and, finally, selected the ideal one. This was further documented by Gevers, Mohammed, and Baytalskaya (2015) who suggested that procrastination might be an incubation period for creativity. In addition, Díaz-Morales et al (2008) revealed that the beneficial influence of procrastination on creativity could be due to the preference for imaginative thinking style.…”
Section: Literature Review Procrastination and Creativitymentioning
confidence: 74%